The unintended outcome: a retrospective cross‐sectional study using a urine lateral flow assay to detect ART use reveals non‐disclosure of taking ART in South Africa's public health system - Nsika Sithole; Indira Govender; Matthew Spinelli; Theresa Smit; Siyabonga Cibane; Mlungisi Zwane; Njabulo Phakathi; Meighan Krows; Busisiwe Nkosi; Janet Seeley; Ruanne V. Barnabas; Mark J. Siedner; et al. (Journal of the International AIDS Society, 2025)
Abstract Introduction Differentiated service delivery (DSD) models for HIV and tuberculosis (TB) care prioritize efficient resource allocation and targeted interventions, and benefit from accurate assessment of patients’ antiretroviral therapy (ART) pill‐taking status. Accurate ART use identification is essential for ensuring proper care transition services rather than unnecessary initiation. A point‐of‐care urine tenofovir (TFV) assay may identify undisclosed ART use in settings with high rates of TB and HIV coinfection. Methods A cohort of people living with HIV (PWH) presenting for routine care, including newly diagnosed and those returning to care, and reporting no ART use within 90 days, was enrolled in a clinic‐based cross‐sectional study of TB prevalence which tested for TB using sputum and urine‐based TB tests in two clinics in KwaZulu‐Natal, South Africa. CD4 counts were determined at the time of ART initiation, per national guidelines. A novel urine‐based lateral flow assay (LFA) which detects TFV ingested within the past 4–7 days was used to assess ART use from thawed urine samples, which were collected concurrently with the self‐report assessment. Conditional logistic regression models assessed predictors of ART non‐disclosure. Results Between 12/2021 and 5/2024, 404 PWH (40% male) reporting no recent ART use presented for ART initiation. TB testing identified 14 (3%) PWH with undiagnosed TB. Seventy‐nine (20%) had detectable TFV in urine indicating undisclosed ART use, with a median CD4 count of 466 cells/mm3 (IQR 277–625) compared to 322 cells/mm3 (IQR 175–490, p = 0.001) in those without undisclosed ART use. In a multivariable model, undisclosed ART use was associated with older age, rural clinic site, higher CD4 count and having active TB, but not with gender, education or employment. Conclusions Among people presenting for HIV treatment initiation, 20% had evidence of ART use within 4–7 days by TFV urine LFA testing. Integration of point‐of‐care urine TFV assays into DSD models of HIV care may support providers to engage PWH about treatment challenges, address potential barriers to disclosure and facilitate seamless transfers between clinics. If successful, this strategy may reduce duplicative care entries and promote more efficient use of resources.